Understanding African music – Listen and learn: music made easy – For future generations: Hugh Tracey and the International Library of African Music – Sound of Africa – Music of Africa – Historical recordings by Hugh Tracey – Soul safari series – The Dhow Countries Music Academy: Zanzibar (International Library of African Music, 2016)
pages: 232-239
Keywords: African Music